Nickel Nutrition in Plants - Guodong Liu; Eric H. Simonne; Yuncong Li (EDIS)
This 5-page fact sheet introduces agricultural and horticultural producers to the role and function of the newest identified essential plant nutrient, nickel (Ni). Written by Guodong Liu, E. H. Simonne, and Yuncong Li, and published by the UF Department of Horticultural Sciences, June 2011.